Reforming the Information Support of Public Administration in the Wartime - Iefymenko, T.; Lovinska, L.; Kucheriava, М. (Science and Innovation, 2022)
Introduction. The appropriate database on the effectiveness of the institutional sectors of the Ukrainian economy, including Nonfinancial and Financial corporations and the General Government sector, plays a vital role in decision-making at the state level and the level of institutional investors. Problem Statement. According to the World Bank forecasts, the wartime in Ukraine and a significant reduction in GDP necessitate the attraction of additional finances aiming at economic recovery. These need accurate information, both at the stage of requests for additional funding from international financial institutions and at the accountability and effectiveness assessment stage. Purpose. Developing and substantiating the suggestions to increase the transparency of information on financial and property state and the efficiency of institutional sectors of the economy. Management decisions based on such information can be made at the meso and macro levels during wartime and post-war recovery of the economy. Materials and Methods. The study is based on the following information sources: documents issued by international financial and professional organisations to develop accounting and analytical support for decisionmaking. Research methods used: bibliographic, analysis, synthesis, generalisation and systematisation. Results. The following critical issues of IPSAS implementation for justifying strategic financial decisions during both wartime and the post-war period are identified. It is proved that there may be other areas, related to the further development of the entities’ nonfinancial reporting in Ukraine. Conclusions. The results of the study have allowed formulating the suggestions for further improvement of the transparency and accountability of institutional sectors and developing a potentially informational solid and analytical database for strategic decision-making.